2009
DOI: 10.3149/jms.1701.31
|View full text |Cite
|
Sign up to set email alerts
|

Angry Young Men? Masculinities and Emotion among Young Male Activists in the Global Justice Movement

Abstract: PostprintThis is the accepted version of a paper published in Journal of Men's Studies. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Por otra parte, se encontraron estudios sobre las emociones como construcción social (Walton, Coyle, & Lyons, 2004;Brenton & Elliott, 2017), en relación con la construcción de la masculinidad (Buzzanell & Turner, 2003;Emslie, et al, 2006;Evers, 2009;Canham, 2009;Montes, 2013;White, 2014;Mann, Tarrant, & Lesson, 2016), relaciones de poder (Meth, 2009), conocimientos, significados emocionales y subjetividades relacionados con el género (Cruz, 2011;Lively, 2008;Wilkins, 2012;Waitt & Stanes, 2015), como la paternidad (Evans, 2012), el sexo opuesto (Duncombe & Marsden, 1993;Wyatt & Ehrhardt, 2003;Morales de Castro, 2010), vínculos afectivos (Jackson, 2012), expresión, experiencias y regulación emocional en diferentes contextos (Barrientos Delgado., et al, 2011;Zackariasson, 2009;Vaccaro, Schrock, & McCabe, 2011;Bennett & Gough, 2013;Randell, et al, 2015;Apesoa-Varano, Barker, & Hinton, 2015;Nash, 2012), en relación con la salud, cuidado y autocuidado (Lomas, Cartwright Edginton, & Ridge, 2012;Wentzell, 2014;Wu, Oliffe, Bungay, & Johnson, 2015;Thomeer, Reczek, & Umberson, 2015), el cuerpo (Villa, 2015;Waitt & Stanes, 2015) y la violencia, perdón, paz y reconciliación (Conejero, Etxebarria, & Montero, 2014).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Por otra parte, se encontraron estudios sobre las emociones como construcción social (Walton, Coyle, & Lyons, 2004;Brenton & Elliott, 2017), en relación con la construcción de la masculinidad (Buzzanell & Turner, 2003;Emslie, et al, 2006;Evers, 2009;Canham, 2009;Montes, 2013;White, 2014;Mann, Tarrant, & Lesson, 2016), relaciones de poder (Meth, 2009), conocimientos, significados emocionales y subjetividades relacionados con el género (Cruz, 2011;Lively, 2008;Wilkins, 2012;Waitt & Stanes, 2015), como la paternidad (Evans, 2012), el sexo opuesto (Duncombe & Marsden, 1993;Wyatt & Ehrhardt, 2003;Morales de Castro, 2010), vínculos afectivos (Jackson, 2012), expresión, experiencias y regulación emocional en diferentes contextos (Barrientos Delgado., et al, 2011;Zackariasson, 2009;Vaccaro, Schrock, & McCabe, 2011;Bennett & Gough, 2013;Randell, et al, 2015;Apesoa-Varano, Barker, & Hinton, 2015;Nash, 2012), en relación con la salud, cuidado y autocuidado (Lomas, Cartwright Edginton, & Ridge, 2012;Wentzell, 2014;Wu, Oliffe, Bungay, & Johnson, 2015;Thomeer, Reczek, & Umberson, 2015), el cuerpo (Villa, 2015;Waitt & Stanes, 2015) y la violencia, perdón, paz y reconciliación (Conejero, Etxebarria, & Montero, 2014).…”
Section: Resultsunclassified
“…Por otra parte, desde un paradigma interpretativo, se identificaron cuatro estudios bajo el diseño análisis del discurso (Buzzanell & Turner, 2003;Walton, et al, 2004;Morales de Castro, 2010;Cruz, 2011), a partir de un paradigma hermenéutico-dialectico que permitieron identificar los diseños: narrativo (Zackariasson, 2009;White, 2014), estudio de caso (Canham, 2009;Mann, et al, 2016), análisis secundario (Emslie, et al, 2006) y representaciones sociales (Bennett & Gough, 2013), a través de entrevistas, grupo de discusión y foro online respectivamente. Estas últimas técnicas permiten ampliar el panorama de aplicación de métodos en las investigaciones de emociones en hombres (Ramírez Rodríguez, 2017).…”
Section: Discussionunclassified
“…Such collaboration appeared to strengthen their collective identity, affective bonds and associational networks (as della Porta, 2008b). The young adult activists described using only nonviolent tactics, in line with della Porta's (2008a) and Jämte and Ellefsen's (2020) respective scholarship, rather than combining it with other tactics, as some studies found (Sandoval, 2020;Schierup et al, 2014;Zackariasson, 2009). Nonetheless, they did describe friends using violence to respond to neo-Nazis (Reynolds-Stenson & Earl, 2018), but this was mainly during everyday activities, such as outside a pub at night instead of during a demonstration.…”
Section: Political Dimensionsmentioning
confidence: 99%
“…Contemporary youth protest movements rarely embrace violent tactics exclusively or promote their widespread use, instead integrating them alongside other non-violence tactics (Loukakis & Portos, 2020). This is shown by Zackariasson (2009) in the 2001 Global Justice protests in Gothenburg, Schierup et al, (2014) in the 2013 Stockholm riots in the Husby neighbourhood and Sandoval (2020) in the most recent student protests in Chile.…”
Section: Existing Researchmentioning
confidence: 99%
“…Emotions, in particular, have received a great deal of scholarly attention (see Jasper ). Social movements researchers have investigated how emotions foster solidarity (Nepstad ; Summers‐Effler ), promote participation and mobilization (Benski ; Wettergren ; Zchariasson ) or demobilization and non‐participation (Kleres, ; Norgaard ), and provide a route for protests (Yang ). They have also studied the interactional processes of emotion management among activists and social movement groups (Groves ; Hercus ; Reger ).…”
mentioning
confidence: 99%